2018
DOI: 10.3390/toxins10080319
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Analysis of Twelve Mycotoxins in Corn and Corn-Derived Products by LC-MS/MS to Evaluate the Carry-Over Ratio during Wet-Milling

Abstract: This study investigated the distribution of twelve mycotoxins (aflatoxins B1, B2, G1, and G2; ochratoxin A; fumonisins B1 and B2; deoxynivalenol; nivalenol; zearalenone; T-2 toxin; and HT-2 toxin) in corn and corn by-products (corn bran, cornstarch, corn gluten, corn gluten feed, corn germ, light steep water, and corn steep liquor) produced by wet-milling in Korea. Fifty-two samples were collected from three factories producing cornstarch and other corn by-products. The samples were pretreated on an immunoaffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…The mean total aflatoxin concentrations of the corn samples in 2018 (2.432 µg/kg) and in 2019 (1.745 µg/kg) analyzed in the present study were lower than the results reported by Hinson and Darkwa (2016) in corn wet‐ milling plant in Mankessım (149.9 µg/kg) and higher than the results reported by Park et al. (2018) in corn wet‐milling plant in Korea (max. 0.2 µg/kg).…”
Section: Resultscontrasting
confidence: 79%
“…The mean total aflatoxin concentrations of the corn samples in 2018 (2.432 µg/kg) and in 2019 (1.745 µg/kg) analyzed in the present study were lower than the results reported by Hinson and Darkwa (2016) in corn wet‐ milling plant in Mankessım (149.9 µg/kg) and higher than the results reported by Park et al. (2018) in corn wet‐milling plant in Korea (max. 0.2 µg/kg).…”
Section: Resultscontrasting
confidence: 79%
“…Recently, Park et al. (2018) simultaneously analyzed 12 mycotoxins in corn and by‐products of corn during wet milling and found out that AFB1, DON, and FBs were largely transferred to by‐products. Surprisingly, trace amounts of ZEN (up to 20.5 µg/kg) and OTA (up to 0.2 µg/kg) were also detected in corn starch.…”
Section: The Fate Of Mycotoxins During Food Processing and Their Impamentioning
confidence: 99%
“…In terms of the distribution of DON in whole corn and milled corn fractions, endosperm, germ and pericarp contains 20, 25 and 55% of the original DON of kernel, respectively [15]. Meanwhile, ZEN is reported to be evenly distributed during the milling process in all corn byproducts except corn starch [16]. It is notable that the most obvious ZEN and DON contaminations occur during the period of preharvest crops.…”
Section: Introductionmentioning
confidence: 99%